Treatment of Medial Patellar Instability With Bipolar Patellofemoral Cartilage Lesions: Staged De-rotational Distal Femoral Osteotomy Followed by Bipolar Osteochondral Allograft Transplantation and Tibial-Tubercle Osteotomy - Benjamin Lurie MD; George F. Hatch MD (SAGE Publishing, 2024)
Background: Patellar instability with symptomatic cartilage lesions in young patients is a challenging problem to treat. The use of osteotomies to correct malalignment and fresh osteochondral allograft transplantation (OCA) to address cartilage lesions and patellofemoral dysplasia is a viable treatment option for carefully selected patients. Indications: The patient is a 22-year-old woman with medial patellar instability caused by iatrogenic distal femoral external rotation and uncontained grade IV patellofemoral lesions. The patient was indicated for OCA because the lesions were too large for an osteochondral autograft transfer system (OATS) and were uncontained and not amenable to autologous chondrocyte implantation. Bipolar OCA also addresses the patient's patellofemoral dysplasia by restoring a more morphologically normal patellofemoral joint. The external rotation and mild varus deformity are corrected with a biplanar distal femoral osteotomy. Correction of malalignment is necessary prior to OCA transplantation to avoid abnormal graft loading and thereby decrease the risk of graft failure. Technique Description: (1) Diagnostic arthroscopy and fluoroscopic examination under anesthesia. (2) Lateral closing wedge de-rotational distal femoral osteotomy. (3) Bipolar OCA with tibial tubercle osteotomy and removal of hardware. Results: In this case, the patient had significant improvement in her symptoms and had full knee range of motion with a normal gait at 3 months after surgery. Depending on a patient's preoperative function and the specific pathology, full recovery can take considerably longer. A successful outcome is considered return to activities of daily living without significant pain. Return to higher level athletic activities is significantly more unpredictable. Graft survival of bipolar patellofemoral OCA is variable, and the literature is limited by the small number of procedures performed, but published series range from 60% to 85% at 5 years. Discussion/Conclusion: A successful outcome in these unique, complex cases depends on good patient selection, preoperative planning, and surgical execution. Patellar instability can be reliably treated when the predisposing anatomical factors are appropriately corrected. Bipolar OCA can provide significant improvement in pain and function, but continues to have the highest rate of graft failure compared with other sites within the knee, and should be considered a salvage operation for patients with significant limitations in activities of daily living. Patient Consent Disclosure Statement: The author(s) attests that consent has been obtained from any patient(s) appearing in this publication. If the individual may be identifiable, the author(s) has included a statement of release or other written form of approval from the patient(s) with this submission for publication.